2017
DOI: 10.1186/s40066-016-0079-z
|View full text |Cite
|
Sign up to set email alerts
|

Livestock ownership, animal source foods and child nutritional outcomes in seven rural village clusters in Sub-Saharan Africa

Abstract: Background: Sub-Saharan Africa currently has the highest prevalence of malnutrition worldwide. In children under the age of 5 years, malnutrition can have long-term effects on physical and cognitive development, with implications at the national scale. Theoretically, livestock-based interventions are well placed to overcome constraints faced by micronutrient and/or food-based interventions. However, there is limited empirical evidence to support this hypothesis. Methods:This study utilised agriculture, nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 40 publications
(51 reference statements)
2
67
0
1
Order By: Relevance
“…The fact that all three foods had similar results in terms of impact on nutritional status could reflect a more systemic nonfood-related phenomenon in the environment. For example, exposure to environmental hazards may limit the benefits of ASFs through effects on gut integrity (Hetherington, Wiethoelter, Negin, & Mor, 2017;Kaur, Graham, & Eisenberg, 2017). Children may suffer from environmental enteric dysfunction, which has been associated with stunting by inflammation-mediated interference with the insulin-growth factor synthesis pathway and through negative impacts on absorption of nutrients (Owino et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that all three foods had similar results in terms of impact on nutritional status could reflect a more systemic nonfood-related phenomenon in the environment. For example, exposure to environmental hazards may limit the benefits of ASFs through effects on gut integrity (Hetherington, Wiethoelter, Negin, & Mor, 2017;Kaur, Graham, & Eisenberg, 2017). Children may suffer from environmental enteric dysfunction, which has been associated with stunting by inflammation-mediated interference with the insulin-growth factor synthesis pathway and through negative impacts on absorption of nutrients (Owino et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…No other comparable intervention study was found in young children of resource-poor populations. One observational study reported an inconsistent effect of increased egg consumption on underweight in different rural villages of Sub-Saharan Africa [16]. A large scale study in India associated lower consumption of eggs with a two-fold increased odds of stunting in under two children [17].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Uganda, it is shown that large ruminants ownership increases dairy consumption but has no significant effect on beef consumption, while chicken consumption increases with the number of poultry owned (Azzari, 2014). Similarly, Hetherington et al (2006) study the relationship between livestock ownership and animal-source foods consumption in seven rural villages located in Sub-Saharan Africa and confirm that households with livestock ownership are more likely to consume animal-base foods.…”
Section: Livestock Food Security and Women's Empowermentmentioning
confidence: 90%
“…Azzari et al (2014) show that small ruminant ownership decreases the probability of weight loss and underweight on children between three and five years old, while large ruminant ownership has the opposite effect probably due to animal health issues. Hetherington et al (2006) also show that the link between animal-based foods consumption and anthropometric measurements is not clear, as their findings vary between negative and positive effects, depending on the food commodity and the villages.…”
Section: Livestock Food Security and Women's Empowermentmentioning
confidence: 97%